2009
DOI: 10.2174/1871529x10909040240
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Infective Endocarditis

Abstract: Infective endocarditis (IE) is a lethal disease if not promptly treated with antibiotics, either in association with surgery or not. The incidence of disease has not decreased over the last decades due to the change of risk conditions. Complications of IE may involve cardiac structures when the infection spreads within the heart, or extra cardiac ones when the cause is usually from embolic origin; they may also be due to medical treatment or to the septic condition itself. A variety of complications may occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 0 publications
2
57
0
Order By: Relevance
“…When affecting the left side, the disease has an acute course with a mean duration of illness from onset to diagnosis reported as 15 days, and a significantly higher rate of complications including peripheral embolization (40%), congestive heart failure, valve-ring abscesses, splenic abscesses and neurological sequelae (53% in older studies) [20]. As expected, mortality is high, ranging from 69% in earlier published series to 10% in more contemporary cohorts with improved medical and surgical therapies [20][21][22]. Although earlier studies had noted a mortality benefit with surgical intervention, Reyes et al reported no significant difference in outcome between medical treatment alone versus combined medicosurgical intervention between the 1969-1975 and 2006-2008 time periods [21].…”
Section: Non-hacekmentioning
confidence: 90%
“…When affecting the left side, the disease has an acute course with a mean duration of illness from onset to diagnosis reported as 15 days, and a significantly higher rate of complications including peripheral embolization (40%), congestive heart failure, valve-ring abscesses, splenic abscesses and neurological sequelae (53% in older studies) [20]. As expected, mortality is high, ranging from 69% in earlier published series to 10% in more contemporary cohorts with improved medical and surgical therapies [20][21][22]. Although earlier studies had noted a mortality benefit with surgical intervention, Reyes et al reported no significant difference in outcome between medical treatment alone versus combined medicosurgical intervention between the 1969-1975 and 2006-2008 time periods [21].…”
Section: Non-hacekmentioning
confidence: 90%
“…Indications for emergency or urgent surgery in IE are well known, but there is a large group of patients who develop serious complications in the course of pharmacotherapy, which worsen their prognosis [12].…”
Section: Discussionmentioning
confidence: 99%
“…NTCD endocarditis has been described as an aggressive and destructive disease with frequent thrombo-embolic complications [10,11], which were also observed in this patient. Systemic embolization rates in IE range from 22% to 50%, and neurological complications develop in 20% to 40% of patients [23]. It has been documented that 70% of IE survivors who experience a cardio-embolic stroke achieve full neurological recovery after cardiac surgery [24].…”
Section: Discussionmentioning
confidence: 99%